2017
DOI: 10.1186/s12936-017-1696-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of anti-malarial ozonides against an artemisinin-resistant isolate

Abstract: BackgroundRecently published data suggest that artemisinin derivatives and synthetic peroxides, such as the ozonides OZ277 and OZ439, have a similar mode of action. Here the cross-resistance of OZ277 and OZ439 and four additional next-generation ozonides was probed against the artemisinin-resistant clinical isolate Plasmodium falciparum Cam3.I, which carries the K13-propeller mutation R539T (Cam3.IR539T).MethodsThe previously described in vitro ring-stage survival assay (RSA0–3h) was employed and a simplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…Recent reports on K13-modified isogenic lines have provided evidence that the C580Y mutation does not mediate cross-resistance to OZ439 (refs. 30,89), whereas the rare R539T mutation, in some studies, mediated partial cross-resistance 30,8991 . Of note, a recent phase 2 clinical trial with OZ439 showed a nonstatistically significant trend toward slightly longer parasite clearance half-lives in individuals harboring K13-mutant infections, as compared to those with wild-type K13.…”
Section: Next-generation Antimalarialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports on K13-modified isogenic lines have provided evidence that the C580Y mutation does not mediate cross-resistance to OZ439 (refs. 30,89), whereas the rare R539T mutation, in some studies, mediated partial cross-resistance 30,8991 . Of note, a recent phase 2 clinical trial with OZ439 showed a nonstatistically significant trend toward slightly longer parasite clearance half-lives in individuals harboring K13-mutant infections, as compared to those with wild-type K13.…”
Section: Next-generation Antimalarialsmentioning
confidence: 99%
“…Ongoing clinical studies should clarify whether OZ439 can be effective at treating K13-mutant infections, and whether specific K13 mutations such as R539T might reduce drug efficacy. Importantly, the earlier-generation ozonide OZ277, which is licensed for clinical use in India in combination with piperaquine (Synriam), was recently observed in several studies to lose potency against mutant K13 parasites 30,8991 . These data argue for close pharmacovigilance of treatment outcomes of the OZ277-containing combination, especially given that K13 mutations have been identified in India or near its borders with Myanmar and Bangladesh 93,94 .…”
Section: Next-generation Antimalarialsmentioning
confidence: 99%
“…Recent in vitro studies have used drug pulse activity assays to examine the exposure time dependence of parasite response to selected peroxide antimalarials (34)(35)(36) across the asexual parasite life cycle. The extent of parasite killing was found to be dependent on parasite strain and life cycle stage, drug concentration, and drug exposure time.…”
mentioning
confidence: 99%
“…It was observed that the ringstage parasites were able to develop a quiescent state, which was associated with a mutation in the Kelch 13 propeller domain [3]. In reality, the use of conventional in vitro methods to evaluate the IC 50 of drugs cannot discriminate an artemisinin partially resistant strain from a susceptible one after exposure to DHA, the active metabolite [24]. In order to correlate survival of parasites in vitro with the time of parasitic clearance observable in vivo, the ring-stage survival assay [25] was used where a short pulse of DHA treatment during the early ring stage of the erythrocyte phase allows for observing differences in susceptibility between the sensitive and resistant strain [25].…”
Section: Heparin Quantificationmentioning
confidence: 99%
“…The results show a decrease of toxicity and an improvement in effectiveness. The RSA 0-3 h , which is able to predict the potency of compounds against artemisinin-resistant parasites in malaria patients [24], demonstrated the potent activity of the heparin-targeted liposomes towards an artemisinin-resistant isolate compared to poupartone B alone. Furthermore, it confirmed that this formulation was able to kill resistant parasites, even with a short contact time.…”
Section: Heparin Quantificationmentioning
confidence: 99%